2009
DOI: 10.1051/forest/2008086
|View full text |Cite
|
Sign up to set email alerts
|

Density dependence on tree survival in an old-growth temperate forest in northeastern China

Abstract: Abstract• Density dependence is a major mechanism for shaping plant communities. However, its role in regulating diverse, mixed natural tree communities is less certain.• In this study we investigated density-dependent effects in a large-scale (25 ha) old-growth temperate forest in northeastern China. Spatial patterns of neighborhood distribution in the plot were analyzed using various methods for inferring competition, including (1) pair correlation function to determine spatial patterns of pre-mortality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
2
29
1
1
Order By: Relevance
“…However, due to the limited experimental conditions, we did not include saplings of DBH < 5 cm in our analysis. Therefore, some discrepancies with previous studies may exist in terms of spatial distribution patterns and spatial associations within lower height classes Zhang et al 2007;Zhang et al 2009). In addition, the spatial patterns of species may have been generated by the interplay of various factors, such as selective cutting (Lei et al 2007), forest fire (Yu et al 2009), physiological effects (Peres-Neto and Legendre 2010), and disturbance (Allstadt et al 2012).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…However, due to the limited experimental conditions, we did not include saplings of DBH < 5 cm in our analysis. Therefore, some discrepancies with previous studies may exist in terms of spatial distribution patterns and spatial associations within lower height classes Zhang et al 2007;Zhang et al 2009). In addition, the spatial patterns of species may have been generated by the interplay of various factors, such as selective cutting (Lei et al 2007), forest fire (Yu et al 2009), physiological effects (Peres-Neto and Legendre 2010), and disturbance (Allstadt et al 2012).…”
Section: Resultsmentioning
confidence: 64%
“…With increases in radius, results at coarser distances include information at finer distances within the circle. O-ring statistics can effectively rule out the influence of cumulative effects; they are developed from Ripley's K function by replacing the circles of Ripley's K function with rings, which can isolate specific distance classes and analyze spatial patterns at a given distance r (Fortin and Dale 2005;Hao et al 2007;Xu et al 2009;Zhang et al 2009). O-ring statistics include both univariate and bivariate procedures.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Stoll and Newbery (2005) studied the growth of medium-sized (10 to <100 cm diameter at breast height, dbh) trees of ten abundant overstory dipterocarp species and found strong negative effects of neighbors on their growth in a lowland forest in Borneo. Similarly, Zhang et al (2009) found tree survival was negatively correlated with conspecific basal area for 8 of 13 focal species with dbh ≥ 1 cm in the temperate forest of Changbaishan Mountain, China. Thus, previous studies indicate that negative density dependence exists at both early and later life-history stages of trees.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, NDD can result in lower growth and survival of local abundant species [2]. The supporting results include observational [2][8] and experimental studies [9][13] that take place in tropical [14][17], subtropical [18] and temperate forest [19][22]. Johnson et al [23] even further concluded that NDD explains the latitudinal gradient of tree species richness.…”
Section: Introductionmentioning
confidence: 85%